Comparison of antimicrobial activity of citrus fruit in Malaysia against gram-negative bacteria / Nazihah Nazarudin - Nazarudin, Nazihah (2018)
The demand for bioactive component from natural resources has been increased worldwide for pharmaceutical purpose. The aim of this study is to evaluate the antimicrobial activity of Citrus hystrix, Citrus microcarpa and Citrus aurantifolia of juice and peel plant against gram-negative bacteria using disc diffusion method. Gram-negative bacteria such as E.coli, Salmonella spp and Shigella spp are common types of species that can cause foodborne illness. Overall Salmonella spp is very susceptible against all the Citrus microcarpa, Citrus hystrix and Citrus aurantifolia peel compared to Shigella spp and E.coli spp. The highest inhibition zone recorded among the Citrus peel was from Citrus hystrix with 18.67 mm against Salmonella spp while the lowest is from Citrus microcarpa with 9 mm against Shigella spp. Besides that, the result for Citrus juice shows that all Citrus hystrix, Citrus microcarpa and Citrus aurantifolia are very susceptible to E.coli compared to the Salmonella spp and Shigella spp. The highest inhibition zone recorded is from Citrus hystrix against E.coli with inhibition zone recorded are 16.67 mm while the lowest is comes from C. aurantifolia against Salmonella spp with 8.67 mm. Overall the ANOVA result for the E.coli, Salmonella spp and Shigella spp against Citrus peel of Citrus hystrix, Citrus microcarpa and positive control show there is significance difference. Next, Salmonella spp and Shigella spp against Citrus juice of Citrus hystrix, Citrus microcarpa, Citrus aurantifolia and positive control shown there is significance except for E.coli where there is no siginificance difference against all the Citrus hystrix, Citrus microcarpa, Citrus aurantifolia and positive control because the p values is higher than 0.05. As conclusion, Citrus hystrix, Citrus microcarpa and Citrus aurantifolia peel are very good against Salmonella spp while Citrus hystrix, Citrus microcarpa and Citrus aurantifolia juice is very good against E.coli spp.